LRP6 Polymorphisms Is Associated With Sudden Cardiac Death in Patients With Chronic Heart Failure in the Chinese Han Population - Guo, Qi; Lai, Yiwei; Chu, Jianmin; Chen, Xuhua; Gao, Mingyang; Sang, Caihua; Dong, Jianzeng; Pu, Jielin; Ma, Changsheng (Frontiers in Cardiovascular Medicine, 2022)
Low-density lipoprotein receptor-related protein 6 (LRP6) plays a critical role in cardiovascular homeostasis. The deficiency of LRP6 is associated with a high risk of arrhythmias. However, the association between genetic variations of LRP6 and sudden cardiac death (SCD) remains unknown. This study aims to examine the association between common variants of LRP6 and the prognosis of chronic heart failure (CHF) patients. From July 2005 to December 2009, patients with CHF were enrolled from 10 hospitals in China. The single-nucleotide polymorphism (SNP) rs2302684 was selected to evaluate the effect of LRP6 polymorphisms on the survival of the patients with CHF. A total of 1,437 patients with CHF were finally enrolled for the analysis. During a median follow-up of 61 months, a total of 546 (38.0%) patients died, including 201 (36.8%) cases with SCD and 345 (63.2%) cases with non-SCD. Patients carrying A allele of rs2302684 had an increased risk of all-cause death (adjusted HR 1.452, 95% CI 1.189-1.706; P ＜0.001) and SCD (adjusted HR 1.783, 95% CI 1.337-2.378; P ＜0.001). Therefore, the SNP rs2302684 T＞A in LRP6 indicated higher risks of all-cause death and SCD in patients with CHF. LRP6 might be added as a novel predictor of SCD and could provide an attractive and direct therapeutic target in SCD prevention.